Adipose Tissue Lipokines: Recent Progress and Future Directions - Li, Veronica L. (Diabetes, 2020)
Beyond classical metabolic functions in energy storage and energy expenditure, adipose tissue is also a dynamic endocrine organ that secretes bioactive factors into blood plasma. Historically, studies of the adipose secretome have predominantly focused on polypeptide adipokines. Recently, adipose-derived blood-borne lipids (“lipokines”) have emerged as a distinct class of endocrine factors. Lipokines are intimately connected to intracellular pathways of fatty acid metabolism and therefore uniquely poised to communicate the intracellular energy status of adipocytes to other nonadipose tissues including liver, muscle, and pancreas. Here, we discuss recent progress on our understanding of adipose-secreted lipokines as endocrine regulators of glucose and lipid metabolism. We also provide our perspective on future directions for adipose-secreted lipids, including limitations of the currently available experimental data as well as potential strategies for addressing the remaining open questions.